The implication of lecturers’ academic competency on Malaysian and Indonesian students’ satisfaction - Warul Walidin AK, Sulaiman,; Yusuf, M.; Usman, Jarjani; ., Masrizal (Opción, 2020)
This study investigated the implication of the academic competencies of educators on students’ learning satisfaction at the School of Education and Modern (SEML) University Utara Malaysia (UUM) and the Faculty of Tarbiyah and Teaching (FTK) UIN Ar-Raniry. Based on qualitative data, the lecturers at FTK UIN Ar-Raniry and SEML UUM have good academic competencies in planning, teaching, and evaluation. The finding is also supported by the quantitative data, which is 85.6% have good ability in preparing Rencana Pembelajaran Semester (RPS). 78.8% of lecturers at SEML UUM have good academic competencies in teaching, while in FTK UIN Ar-Raniry 70%.